(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines the role of teachers and teaching in LICS, the policies and supports teachers need, an overview of global education, international education advocacy, and the different ways these global trends are shaping the work of teachers.